The impact of ChatGPT on E-commerce: the case of platform-based business - Lee, Siu Ying (2024)
In this digital era, ChatGPT has offered the world a peek at artificial intelligence and created a lot of discussions about its amazing advancements. Over 200 companies adopted ChatGPT in 2023. Today, certain platform-based business preparing to integrate ChatGPT into their business. Thus, this study will offer useful information to platform-based business thinking about incorporating ChatGPT into their operations, help them to make informed decisions about ChatGPT adoption and resource allocation, enabling them to harness the full potential of ChatGPT in enhancing user experiences and staying ahead in the rapidly evolving digital marketplace. The research objective is to investigate the impacts of ChatGPT on the organizational performance of platform-based businesses by using an integrated TAM and ISSM model. Quantitative research via questionnaires is used for research design to conduct an empirical result. A deeper data analysis of the 386-sample size has been made. It shows that information quality, system quality and service quality of ChatGPT will affect the users’ perceived usefulness, perceived usefulness will affect the user satisfaction, whereas user satisfaction will influence the organizational performance of platform-based business. However, perceived usefulness shows there is no significant relationship with organizational performance. This final year project has provided empirical results and findings for the ChatGPT and platform-based business.